Health research ethics training manual - Nepal Health Research Council (Government of Nepal; Nepal Health Research Council; Ramshah Path, Kathmandu, Nepal, 2023)
The Nepal Health Research Council (NHRC), was established in 1991 by the Government of Nepal (GoN) through an Act of Parliament, is an autonomous apex body. The NHRC aims to promote the quality and ethical standard of health and medical research in the country and provides ethical approval for research in Nepal. Since the establishment of the NHRC, it has facilitated the ethical review committee and has approved 1212 health research proposals in between 1991 to 2014.